Anticorrosive paint, preparation method, application and refrigerator
Through covalent organic framework/functionalized hydroxyapatite modified water-based polyurethane coating, the problem of heavy metal migration in the metal parts in the refrigerator is solved, and efficient anti-corrosion and heavy metal adsorption effects are achieved, which is suitable for applications in high humidity environments of refrigerators.
Patent Information
- Application Number
- CN202411110200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-02-28
AI Technical Summary
Existing anticorrosion coatings cannot effectively prevent heavy metal migration in metal parts inside refrigerators, resulting in food pollution and health risks, and it is difficult to meet anticorrosion requirements in high humidity environments.
The water-based polyurethane coating modified with covalent organic framework/functionalized hydroxyapatite is used to form a coating with high polymerization degree, high cross-linking density and strong stability through the composite of the covalent organic framework and functionalized hydroxyapatite, which has excellent anticorrosion performance and heavy metal adsorption function.
Effectively prevent heavy metals from moving from refrigerator metal parts to internal space, reduce the risk of food pollution, significantly improve the anti-corrosion ability of the paint and heavy metal adsorption performance, and meet the use requirements of the high humidity environment in the refrigerator.
Smart Images

Figure BDA0004991973610000131 
Figure BDA0004991973610000132 
Figure BDA0004991973610000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coatings, and in particular relates to an anti-corrosion coating, a preparation method, an application and a refrigerator. Background Art
[0002] The impact of the EU carbon border adjustment mechanism regulations on the home appliance industry is mainly reflected in promoting the home appliance industry's transition to low-carbon, improving market competitiveness, and responding to potential "carbon barriers". In the refrigerator industry, many internal materials are metal parts. For metal parts, the use of recycled metals from a wide range of sources can achieve carbon reduction for the entire machine, which has a significant effect on reducing carbon emissions. Moreover, consumers also have a strong demand for recycled materials because they are satisfied with their own green consumption psychology.
[0003] However, metal parts in the refrigerator that are in direct contact with food have the risk of heavy metal migration, which can cause food contamination and affect consumers' health. In particular, the high humidity environment inside the refrigerator makes it more likely to cause metal corrosion, increasing the risk of heavy metal dissolution. Since recycled metal comes from scrap metal recycling materials, there are many impurities and heavy metals. If recycled metal is used in the production of metal parts in direct contact with food inside the refrigerator, there is a risk of heavy metal migration. Consumers will inevitably worry about the heavy metal content and heavy metal migration of recycled metal, causing consumers to worry about the use of recycled materials; coupled with the high humidity environment inside the refrigerator, it further limits the use of recycled metal inside the refrigerator. In addition, many countries have clear requirements for the amount of heavy metal migration for metal materials in imported products.
[0004] At present, coating protection is a commonly used metal anti-corrosion method. Although the existing anti-corrosion coating can prevent moisture and corrosive media from penetrating into the metal matrix and improve the corrosion resistance of the metal, due to the special high humidity environment inside the refrigerator and the use of food preservation, the metal parts inside the refrigerator have the requirement to prevent heavy metal migration, which cannot be met by the existing anti-corrosion coating. Therefore, providing a heavy metal adsorption anti-corrosion coating to avoid heavy metal pollution inside the refrigerator is a problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] The present invention aims at the technical problem that the existing anti-corrosion coatings cannot meet the requirements of the metal parts inside the refrigerator for preventing the migration of heavy metals. An anti-corrosion coating with excellent anti-corrosion performance and heavy metal adsorption function, a preparation method, application and a refrigerator are proposed. The anti-corrosion coating is a water-based polyurethane coating modified with a covalent organic skeleton / functionalized hydroxyapatite. The raw materials used are non-toxic and meet the requirements for use in the refrigerator. The anti-corrosion coating of the present invention is a high-polymerization coating with a large cross-linking density and strong stability. It is applied to the metal parts inside the refrigerator and can prevent heavy metals from migrating from the metal parts of the refrigerator to the internal space and causing food contamination.
[0006] In order to achieve the above object, the present invention provides an anticorrosive coating on one hand, and the technical scheme adopted is: an anticorrosive coating, the raw materials for preparing the anticorrosive coating include heavy metal adsorption anticorrosive filler, the heavy metal adsorption anticorrosive filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of the covalent organic framework and the functionalized hydroxyapatite is 7:(3-5); the preparation process of the covalent organic framework / functionalized hydroxyapatite includes the following steps: S1, preparing functionalized hydroxyapatite containing epoxy groups, S2, according to the mass ratio (3-5):7, the functionalized hydroxyapatite is loaded to the covalent organic framework, and the covalent organic framework / functionalized hydroxyapatite is obtained. It can be understood that according to actual conditions, the mass ratio of the covalent organic framework and the functionalized hydroxyapatite can be adjusted within the above range by a technician in this field, for example, the mass ratio of the two can also be 7:3, 7:4, 7:5.
[0007] Preferably, the S1 step specifically includes the following steps: S1.1, preparing a mixed solution of ethanol and deionized water, adjusting the pH value of the mixed solution to 3-4, and then adding KH560 solution thereto to obtain a mixed solution A; S1.2, weighing hydroxyapatite and dissolving it in deionized water, after ultrasonic dispersion, adding the aqueous solution of hydroxyapatite to the mixed solution A, heating in a water bath and magnetic stirring, the reaction time is 2 hours, to obtain functionalized hydroxyapatite.
[0008] Preferably, the S2 step specifically includes the following steps: S2.1, adding the functionalized hydroxyapatite and the covalent organic framework into an N,N-dimethylformamide solution in a mass ratio of (3 to 5):7, and obtaining a mixed solution B by ultrasonic dispersion; S2.2, heating the mixed solution B in a water bath and magnetically stirring the mixture for 8 hours to obtain a covalent organic framework / functionalized hydroxyapatite.
[0009] Preferably, the covalent organic framework is at least one of TpPa-1, TpPa-2, and TpBD.
[0010] Preferably, the raw materials for preparing the anti-corrosion coating also include water-based polyurethane emulsion, dispersant, thickener, defoamer and leveling agent.
[0011] Preferably, the raw materials for preparing the anti-corrosion coating include the following components in parts by weight: 80-100 parts of the aqueous polyurethane emulsion, 50-60 parts of the heavy metal adsorption anti-corrosion filler, 2-3 parts of the dispersant, 1-3 parts of the thickener, 0.5-1 parts of the defoamer, and 0.2-0.8 parts of the leveling agent. It can be understood that, according to actual conditions, those skilled in the art can adjust the weight proportions of each component within the above range. For example, the weight proportions of the aqueous polyurethane emulsion can also be 80 parts, 85 parts, 90 parts, 95 parts, 100 parts or any value within the above range, the weight proportions of the heavy metal adsorption anticorrosive filler can also be 50 parts, 55 parts, 60 parts or any value within the above range, the weight proportions of the dispersant can also be 2 parts, 2.5 parts, 3 parts or any value within the above range, the weight proportions of the thickener can also be 1 part, 2 parts, 3 parts or any value within the above range, the weight proportions of the defoamer can also be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts or any value within the above range, and the weight proportions of the leveling agent can also be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or any value within the above range.
[0012] On the other hand, the present invention provides a method for preparing the above-mentioned anti-corrosion coating, which specifically comprises the following steps: D1, adding the aqueous polyurethane emulsion, the heavy metal adsorption anti-corrosion filler, the dispersant, the leveling agent and the defoaming agent in parts by weight and stirring thoroughly; D2, adding a thickener and stirring again to obtain the anti-corrosion coating.
[0013] Preferably, during stirring in step D1, the stirring speed is set to 800-1000 rpm, and the stirring time is set to 20 min; during stirring in step D2, the stirring speed is set to 500-600 rpm, and the stirring time is set to 5 min.
[0014] The present invention also provides an application of the above-mentioned anti-corrosion coating, wherein the anti-corrosion coating is applied to the surface of recycled metal to form a coating to achieve anti-corrosion and heavy metal adsorption functions.
[0015] The present invention also provides a refrigerator, wherein the metal parts inside the refrigerator are made of the recycled metal coated with the anti-corrosion paint.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are: the anti-corrosion coating of the present invention has both anti-corrosion and heavy metal adsorption capabilities, which can prevent recycled metal from directly contacting food, while greatly reducing the risk of heavy metal dissolution, eliminating consumers' concerns about the use of recycled metals; the covalent organic skeleton / functionalized hydroxyapatite-modified water-based polyurethane coating of the present invention can effectively prevent heavy metal components from migrating to the internal space of the refrigerator. On the one hand, the interior of the refrigerator is a high-humidity environment and contains a lot of corrosive media. The coating has excellent anti-corrosion ability and can significantly reduce the chance of recycled metal being corroded. On the other hand, it can block food from recycled metal parts to avoid direct contact between the two. Even if the corrosive medium penetrates the coating to cause corrosion of the recycled metal and dissolution of heavy metals, the dissolved heavy metals will be absorbed by the hydroxyapatite in the coating, thereby passivating and fixing. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The embodiment of the present invention provides an anticorrosive coating, a preparation method, an application and a refrigerator. The raw materials for preparing the anticorrosive coating of the present invention include heavy metal adsorption type anticorrosive filler, the heavy metal adsorption type anticorrosive filler is a covalent organic skeleton / functionalized hydroxyapatite, and the mass ratio of the covalent organic skeleton to the functionalized hydroxyapatite is 7:(3-5); the preparation process of the covalent organic skeleton / functionalized hydroxyapatite includes the following steps: S1, preparing functionalized hydroxyapatite containing epoxy groups, S2, according to the mass ratio (3-5):7, the functionalized hydroxyapatite is loaded onto the covalent organic skeleton to obtain the covalent organic skeleton / functionalized hydroxyapatite. The covalent organic skeleton / functionalized hydroxyapatite-modified waterborne polyurethane coating of the present invention can effectively prevent heavy metal components from migrating to the internal space of the refrigerator, can significantly reduce the probability of recycled metal being corroded, and can also block food and recycled metal parts to avoid direct contact between the two. Even if the corrosive medium penetrates the coating to cause recycled metal corrosion and heavy metal dissolution, the dissolved heavy metals will be absorbed by the hydroxyapatite in the coating, thereby passivating and fixing, and has both anti-corrosion and heavy metal adsorption capabilities.
[0019] The present invention prepares the functionalized hydroxyapatite containing epoxy groups in step S1 specifically including: S1.1, preparing a mixed solution of ethanol and deionized water, adding acetic acid to adjust the pH value of the mixed solution to 3-4, and then dropping KH560 solution therein to obtain a mixed solution A; S1.2, weighing hydroxyapatite and dissolving it in deionized water, uniformly dispersing it by ultrasonication, adding the aqueous solution of hydroxyapatite to the mixed solution A, heating it in a water bath, stirring it by magnetic force, and reacting for 2 hours to obtain functionalized hydroxyapatite. In the above steps, acetic acid is used as a catalyst, and under acidic conditions, the methoxyl group of KH560 is first hydrolyzed to generate hydroxyl group, and the hydrolysis is ensured to be complete for 15-20 minutes, and then hydroxyapatite is added, and the hydroxyl group of KH560 can be dehydrated and condensed with the hydroxyl group of hydroxyapatite, thereby functionalizing the hydroxyapatite, and the functionalized hydroxyapatite at this time contains epoxy groups.
[0020] The present invention loads the functionalized hydroxyapatite onto a covalent organic framework in step S2, which specifically includes: S2.1, adding the functionalized hydroxyapatite and the covalent organic framework to an N,N-dimethylformamide solution in a mass ratio of (3-5):7, and obtaining a mixed solution B by ultrasonic dispersion; S2.2, heating the mixed solution B in a water bath, and magnetically stirring the mixed solution B for 8 hours to obtain a covalent organic framework / functionalized hydroxyapatite. In the above steps, the epoxy groups of the functionalized hydroxyapatite are covalently bonded to the amino groups of the covalent organic framework, so that the functionalized hydroxyapatite is loaded onto the covalent organic framework to obtain the covalent organic framework / functionalized hydroxyapatite.
[0021] In a preferred embodiment, the covalent organic skeleton is at least one of TpPa-1, TpPa-2 or TpBD, preferably TpPa-1 with good chemical stability. The covalent organic skeleton is a typical two-dimensional nanomaterial that can enhance the anti-corrosion ability of waterborne polyurethane coatings through physical shielding effects. Since hydroxyapatite is prone to agglomeration, the heavy metal ion adsorption function will be seriously reduced. The covalent organic skeleton in the present invention is compounded with hydroxyapatite through covalent bonds, which improves the dispersibility of hydroxyapatite in waterborne polyurethane coatings, and the covalent organic skeleton has a higher specific surface area and a large number of amino groups, which provide more active sites and are conducive to the dispersion of hydroxyapatite. In addition, the amino groups of the covalent organic skeleton and waterborne polyurethane are easy to form coordination bonds with heavy metal ions with large radius and easy polarization, and play a synergistic role with hydroxyapatite to jointly improve the heavy metal adsorption capacity of the coating.
[0022] The anti-corrosion coating provided in the embodiment of the present invention is prepared from raw materials that also include other components such as aqueous polyurethane emulsion, dispersant, thickener, defoamer and leveling agent. In terms of parts by weight, the raw material components include: 80-100 parts of aqueous polyurethane emulsion, 50-60 parts of heavy metal adsorption anti-corrosion filler, 2-3 parts of dispersant, 1-3 parts of thickener, 0.5-1 parts of defoamer, and 0.2-0.8 parts of leveling agent. The raw materials used in this solution are all non-toxic and meet the requirements for use in refrigerators. The obtained high-polymerization coating has a large cross-linking density and strong stability. Hydroxyapatite has ion exchangeability, among which Ca 2+ It can exchange with heavy metal ions, and phosphate combines with heavy metal ions to form phosphate precipitates, which can adsorb heavy metal ions in metal parts and passivate them; and there are a large number of small pores on the surface of hydroxyapatite, with a high specific surface area, which can provide more sites for adsorbing heavy metal ions.
[0023] In a preferred embodiment, the dispersant is selected from at least one of WCA-80, BYK-194N, and HY-4010; the function of the dispersant in the present invention is to improve the dispersion performance of the anti-corrosion coating, improve the fluidity and coating performance of the anti-corrosion coating, thereby enhancing the adhesion and durability of the anti-corrosion coating.
[0024] In a preferred embodiment, the thickener is selected from at least one of HEUR-A, HEUR-B, HEUR-C, HEUR-D, HEUR-01, and HEUR-122; the thickener in the present invention functions to increase the viscosity and hiding power of the anti-corrosion coating and improve the adhesion of the anti-corrosion coating.
[0025] In a preferred embodiment, the defoaming agent is selected from at least one of BYK-020, BYK-021, BYK-022, BYK-023, BYK-024, BYK-025, BYK-026, BYK-027, and BYK-028; the function of the defoaming agent in the present invention is to reduce the surface tension of the anti-corrosion coating, reduce the generation of foam, ensure the anti-corrosion effect, and extend the service life of the coating.
[0026] In a preferred embodiment, the leveling agent is selected from at least one of DC-57, BYK333, and TEGO450; the function of the leveling agent in the present invention is to improve the leveling and uniformity of the anti-corrosion coating, thereby improving the appearance and quality of the coating.
[0027] The preparation method of the above-mentioned anticorrosive coating of the present invention specifically comprises the following steps: D1, adding waterborne polyurethane emulsion, heavy metal adsorption anticorrosive filler, dispersant, leveling agent and defoamer according to weight proportions, and stirring for 20 minutes at a speed of 800-1000rpm; D1, adding thickener, adjusting the speed to 500-600rpm, and continuing stirring for 5 minutes to obtain heavy metal adsorption anticorrosive coating. In the above steps, covalent organic skeleton / functionalized hydroxyapatite is added to the waterborne polyurethane coating as a filler, and the above mixture is stirred for 20 minutes at a speed of 800-1000rpm by a coating stirring and dispersing machine to improve the dispersibility of the filler; the surface of the covalent organic skeleton / functionalized hydroxyapatite contains amino groups, which have good compatibility with waterborne polyurethane through the principle of similar dissolution, and are evenly dispersed in the waterborne polyurethane, and the obtained anticorrosive coating has both anticorrosion and heavy metal adsorption capabilities.
[0028] The present invention also provides the application of the anti-corrosion coating listed in the above technical solution on the surface of recycled metal.
[0029] The present invention also provides a refrigerator, wherein the metal parts inside the refrigerator are made of the recycled metal coated with the anti-corrosion paint.
[0030] In order to more clearly and in detail introduce the anti-corrosion coating, preparation method, application and refrigerator provided by the embodiments of the present invention, a description will be given below in conjunction with specific embodiments.
[0031] Example 1
[0032] Raw material components: in parts by weight, 90 parts of water-based polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption anti-corrosion filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0033] The preparation method of the anticorrosive coating of this embodiment specifically comprises the following steps:
[0034] (1) Preparation steps of functionalized hydroxyapatite
[0035] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0036] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0037] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0038] The prepared functionalized hydroxyapatite and 1.75 g of the covalent organic framework were added into 100 mL of N,N-dimethylformamide solution, and dissolved uniformly by ultrasonication for 20 min to obtain a mixed solution B;
[0039] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and magnetically stirred at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:4;
[0040] (3) Preparation steps of coating
[0041] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the above mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0042] Example 2
[0043] Raw material components: in parts by weight, 100 parts of water-based polyurethane emulsion, 50 parts of heavy metal adsorption anti-corrosion filler, 2 parts of dispersant, 3 parts of thickener, 1 part of defoamer, and 0.8 parts of leveling agent, wherein the heavy metal adsorption anti-corrosion filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0044] The preparation method of the anticorrosive coating of this embodiment specifically comprises the following steps:
[0045] (1) Preparation steps of functionalized hydroxyapatite
[0046] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0047] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0048] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0049] The prepared functionalized hydroxyapatite and 1.75 g of the covalent organic framework were added into 100 mL of N,N-dimethylformamide solution, and dissolved uniformly by ultrasonication for 20 min to obtain a mixed solution B;
[0050] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and magnetically stirred at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:4;
[0051] (3) Preparation steps of coating
[0052] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the above mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0053] Example 3
[0054] Raw material components: in parts by weight, 80 parts of water-based polyurethane emulsion, 60 parts of heavy metal adsorption anti-corrosion filler, 3 parts of dispersant, 1 part of thickener, 0.5 parts of defoamer, and 0.2 parts of leveling agent. Among them, the heavy metal adsorption anti-corrosion filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0055] The preparation method of the anticorrosive coating of this embodiment specifically comprises the following steps:
[0056] (1) Preparation steps of functionalized hydroxyapatite
[0057] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0058] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0059] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0060] The prepared functionalized hydroxyapatite and 1.75 g of the covalent organic framework were added into 100 mL of N,N-dimethylformamide solution, and dissolved uniformly by ultrasonication for 20 min to obtain a mixed solution B;
[0061] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and magnetically stirred at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:4;
[0062] (3) Preparation steps of coating
[0063] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the above mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0064] Example 4
[0065] Raw material components: in parts by weight, 90 parts of water-based polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption anti-corrosion filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:3.
[0066] The preparation method of the anticorrosive coating of this embodiment specifically comprises the following steps:
[0067] (1) Preparation steps of functionalized hydroxyapatite
[0068] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0069] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0070] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0071] The prepared functionalized hydroxyapatite and 2.33 g of the covalent organic framework were added into 100 mL of N,N-dimethylformamide solution, and dissolved uniformly by ultrasonication for 20 min to obtain a mixed solution B;
[0072] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and magnetically stirred at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:3;
[0073] (3) Preparation steps of coating
[0074] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the above mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0075] Example 5
[0076] Raw material components: in parts by weight, 90 parts of water-based polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption anti-corrosion filler is covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:5.
[0077] The preparation method of the anticorrosive coating of this embodiment specifically comprises the following steps:
[0078] (1) Preparation steps of functionalized hydroxyapatite
[0079] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0080] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0081] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0082] The prepared functionalized hydroxyapatite and 1.4 g of the covalent organic framework were added into 100 mL of N,N-dimethylformamide solution, and dissolved uniformly by ultrasonication for 20 min to obtain a mixed solution B;
[0083] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and magnetically stirred at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:5;
[0084] (3) Preparation steps of coating
[0085] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the above mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0086] Comparative Example 1
[0087] Raw material components: in parts by weight, 90 parts of aqueous polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption anti-corrosion filler is a mixture of covalent organic skeleton and functionalized hydroxyapatite, and the mass ratio of covalent organic skeleton to functionalized hydroxyapatite is 7:4.
[0088] The preparation method of the anticorrosive coating of this comparative example specifically comprises the following steps:
[0089] (1) Preparation steps of functionalized hydroxyapatite
[0090] According to the mass ratio of ethanol to deionized water of 1:5, 15 mL of a mixed solution of ethanol and deionized water was prepared; acetic acid was added to the mixed solution to adjust the pH value of the solution to 3-4, and then 1 mL of KH560 solution was added dropwise thereto to obtain a mixed solution A;
[0091] Weigh 1 g of hydroxyapatite and dissolve it in 10 mL of deionized water. Disperse it evenly by ultrasonication. After 15-20 min, add the aqueous solution of hydroxyapatite to the mixed solution A. Heat in a water bath at 60° C. and stir magnetically at 350-600 rpm for 2 h to obtain functionalized hydroxyapatite.
[0092] (2) Preparation steps of coating
[0093] Add water-based polyurethane emulsion, a mixture of covalent organic framework and functionalized hydroxyapatite, a dispersant, a leveling agent and a defoaming agent into a plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0094] Comparative Example 2
[0095] Raw material components: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, 0.5 parts of leveling agent, wherein the heavy metal adsorption anti-corrosion filler is a covalent organic skeleton.
[0096] The preparation method of the anticorrosive coating of this comparative example specifically comprises the following steps:
[0097] Add water-based polyurethane emulsion, covalent organic framework, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0098] Comparative Example 3
[0099] Raw material components: in parts by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, 0.5 parts of leveling agent, wherein the heavy metal adsorption anti-corrosion filler is hydroxyapatite.
[0100] The preparation method of the anticorrosive coating of this comparative example specifically comprises the following steps:
[0101] Add water-based polyurethane emulsion, hydroxyapatite, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the mixture at a speed of 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0102] Comparative Example 4
[0103] Raw material components: by weight, 90 parts of waterborne polyurethane emulsion, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent.
[0104] The preparation method of the anticorrosive coating of this comparative example specifically comprises the following steps:
[0105] Add water-based polyurethane emulsion, dispersant, leveling agent and defoamer to the plastic cup according to weight proportions, and use a paint stirring and dispersing machine to fully stir the mixture at a speed of 800-1000 rpm for 20 minutes. Then add the thickener, adjust the speed of the paint stirring and dispersing machine to 500-600 rpm, and continue stirring for 5 minutes to obtain an anti-corrosion coating.
[0106] Performance Testing
[0107] The anticorrosion coatings prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to anticorrosion performance tests and heavy metal adsorption performance tests, respectively, as follows:
[0108] 1. Anti-corrosion performance test
[0109] The anticorrosive coatings prepared in Examples 1-5 and Comparative Examples 1-4 were applied to an area of 1*1 cm 2 The working electrode was made on the carbon steel. The three-electrode system was obtained by using the carbon steel with anti-corrosion coating as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet as the counter electrode. The test medium was 3.5wt.% NaCl solution. The open circuit potential of the working electrode was measured using the three-electrode system and CHI-660E electrochemical workstation. When the working electrode was immersed for 30 minutes, the open circuit potential reached a stable state. The data at this time was recorded. The detailed data is shown in Table 1.
[0110] Table 1 Open circuit potential of Examples 1-5 and Comparative Examples 1-4
[0111]
[0112] 2. Heavy metal adsorption performance test
[0113] 50 mg of potassium chromate was added to 100 mL of deionized water to prepare a Cr(VI) solution, 0.1 mol / L of hydrochloric acid was added dropwise to adjust the pH of the solution to 3 (pH=3 is a common value for adsorption experiments), and then 50 mg of the anti-corrosion coating prepared in Example 1 was added. The mixed solution was fully adsorbed at 180 rpm in an oscillation chamber at 25°C for 10 hours, and the removal rate (R, %) of Cr(VI) was calculated. Detailed data are shown in Table 2.
[0114] According to the above steps, the adsorption test solutions of Examples 2-3 and Comparative Examples 1-4 were prepared respectively, and the removal rate (R, %) of Cr(VI) was calculated. The detailed data are shown in Table 2.
[0115]
[0116] Where C0 represents the concentration of Cr(VI) before adsorption, C e It indicates the concentration of Cr(VI) when the adsorption reaches equilibrium.
[0117] Table 2 Cr(VI) removal rates of Examples 1-5 and Comparative Examples 1-4
[0118]
[0119]
[0120] Referring to the performance test results in Table 1 and Table 2, it can be seen that the open circuit potential of Examples 1-5 is significantly improved compared with Comparative Examples 1-4, indicating that the anti-corrosion coatings of the embodiments of the present invention have a stronger ability to resist corrosion; when the heavy metal adsorption test reaches a stable state, the removal rates of Examples 1-5 are significantly higher than those of the comparative examples, proving that the anti-corrosion coatings of the embodiments of the present invention have the ability to adsorb heavy metals, and the addition of covalent organic framework / functionalized hydroxyapatite can effectively enhance the anti-corrosion and heavy metal adsorption functions of the waterborne polyurethane coating. It can be seen from the performance test results of Examples 1-5 that Example 1 has the highest open circuit potential and Cr(VI) removal rate, indicating that when the raw material components are proportioned according to Example 1, the prepared anti-corrosion coating has the best corrosion resistance and heavy metal adsorption performance. This is because the covalent organic skeleton / functionalized hydroxyapatite is uniformly dispersed in the waterborne polyurethane coating through a similar miscible mechanism, thereby improving the corrosion resistance and heavy metal adsorption performance of the coating. The corrosion resistance and heavy metal adsorption performance of the anti-corrosion coating prepared in Example 3 are lower than those in Examples 1 and 2, indicating that excessive covalent organic skeleton / functionalized hydroxyapatite is difficult to dissolve in the waterborne polyurethane coating, which will lead to a decrease in dispersibility. The open circuit potential and Cr(VI) removal rate of Examples 4-5 are lower than those in Example 1, which means that when the mass ratio of the covalent organic skeleton and the functionalized hydroxyapatite is 7:4, the anti-corrosion coating has the best corrosion resistance and heavy metal adsorption performance, that is, the optimal mass ratio of the covalent organic skeleton and the functionalized hydroxyapatite is 7:4.
[0121] Compared with Example 1, the heavy metal adsorption anti-corrosion filler in Comparative Example 1 is a mixture of a covalent organic framework and functionalized hydroxyapatite. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 1 are lower than those of Example 1. This is because the covalent organic framework and hydroxyapatite exist separately in Comparative Example 1, and both will undergo different degrees of agglomeration due to their own high specific surface energy, thereby reducing the corrosion resistance and heavy metal adsorption capacity of the anti-corrosion coating.
[0122] Compared with Example 1, the heavy metal adsorption anti-corrosion filler in Comparative Example 2 is a covalent organic skeleton. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 2 are lower than those of Example 1, indicating that an excessive amount of the covalent organic skeleton is used, which will agglomerate itself, resulting in defects in the interface between it and the polyurethane, thereby reducing the corrosion resistance.
[0123] Compared with Example 1, the heavy metal adsorption anti-corrosion filler in Comparative Example 3 is hydroxyapatite. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 3 are lower than those of Example 1, indicating that the hydroxyapatite is excessive and its own agglomeration phenomenon leads to decreased corrosion resistance and heavy metal adsorption capacity; on the one hand, the agglomeration phenomenon leads to interface defects, which easily become the diffusion path of the corrosive medium, reducing the corrosion resistance; on the other hand, the surface area of the agglomerated hydroxyapatite is greatly reduced, which significantly reduces its contact sites with heavy metals, thereby damaging its heavy metal adsorption capacity.
[0124] Comparative Example 4 does not use heavy metal adsorption anti-corrosion filler. The heavy metal adsorption anti-corrosion filler in Comparative Example 2 is a covalent organic skeleton. According to the performance test results, compared with Comparative Example 4, the Cr(VI) removal rate of Comparative Example 2 is increased and the heavy metal adsorption capacity is enhanced, indicating that the amino group of the covalent organic skeleton forms a coordination bond with the chromium ions to play a role in adsorbing heavy metals.
[0125] In summary, the anti-corrosion coating of the embodiment of the present invention can significantly improve the anti-corrosion and heavy metal adsorption properties of the composite resin by using covalent organic framework / functionalized hydroxyapatite as filler, and is suitable for preparing coatings for internal metal parts of refrigerators.
[0126] The above-described embodiments are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations, modifications, evolutions, and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the scope of protection determined by the claims of the present invention.
Claims
1. An anticorrosive coating, characterized in that: The raw materials for preparing the anti-corrosion coating include heavy metal adsorption anti-corrosion fillers, The heavy metal adsorption anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of the covalent organic framework to the functionalized hydroxyapatite is 7:(3-5); The preparation process of the covalent organic framework / functionalized hydroxyapatite comprises the following steps: S1. preparing functionalized hydroxyapatite containing epoxy groups, S2. According to the mass ratio of (3-5):7, the functionalized hydroxyapatite is loaded onto a covalent organic framework to obtain the covalent organic framework / functionalized hydroxyapatite.
2. The anticorrosive coating according to claim 1, characterized in that: The S1 step specifically includes the following steps: S1.1, prepare a mixed solution of ethanol and deionized water, adjust the pH value of the mixed solution to 3-4, and then add KH560 solution dropwise thereto to obtain a mixed solution A; S1.
2. Weigh hydroxyapatite and dissolve it in deionized water. After uniform dispersion by ultrasonication, add the aqueous solution of hydroxyapatite into mixed solution A. Heat in a water bath and stir magnetically for 2 hours to obtain functionalized hydroxyapatite.
3. The anticorrosive coating according to claim 1, characterized in that: The S2 step specifically includes the following steps: S2.1, adding the functionalized hydroxyapatite and the covalent organic framework into an N,N-dimethylformamide solution in a mass ratio of (3-5):7, and obtaining a mixed solution B by ultrasonic dispersion; S2.
2. Heat the mixed solution B in a water bath and stir it magnetically for 8 hours to obtain a covalent organic framework / functionalized hydroxyapatite.
4. The anticorrosive coating according to claim 3, characterized in that: The covalent organic framework is at least one of TpPa-1, TpPa-2, and TpBD.
5. The anticorrosive coating according to claim 1, characterized in that: The raw materials for preparing the anticorrosive coating also include water-based polyurethane emulsion, dispersant, thickener, defoamer and leveling agent.
6. The anticorrosive coating according to claim 5, characterized in that: In terms of weight parts, the raw materials for preparing the anti-corrosion coating include the following components: 80-100 parts of the aqueous polyurethane emulsion, 50-60 parts of the heavy metal adsorption anti-corrosion filler, 2-3 parts of the dispersant, 1-3 parts of the thickener, 0.5-1 parts of the defoamer, and 0.2-0.8 parts of the leveling agent.
7. The method for preparing the anticorrosive coating according to claim 6, characterized in that: The preparation method of the anticorrosive coating specifically comprises the following steps: D1. Add the aqueous polyurethane emulsion, the heavy metal adsorption anticorrosive filler, the dispersant, the leveling agent and the defoamer in parts by weight and stir thoroughly; D2. Add thickener and stir again to obtain anti-corrosion coating.
8. The method for preparing the anticorrosive coating according to claim 7, characterized in that: During the stirring in step D1, the stirring speed is set to 800-1000 rpm and the stirring time is set to 20 min; During stirring in step D2, the stirring speed is set to 500-600 rpm, and the stirring time is set to 5 min.
9. The use of the anticorrosive coating according to any one of claims 1 to 6, characterized in that: The anti-corrosion paint is applied on the surface of the recycled metal to form a coating to achieve the functions of anti-corrosion and heavy metal adsorption.
10. A refrigerator, characterized in that: The metal parts inside the refrigerator are made of the recycled metal coated with the anti-corrosion paint as claimed in claim 9.
Citation Information
Patent Citations
Hydroxyapatite nanosheet composite anticorrosive paint as well as preparation method and application thereof
CN111978828A
Aqueous coating liquid and functional coating film
JP2007145977A